Modified Kuppuswamy scale 2026: methodological comparison of approaches for updating income classification - Katre, Rohit; Singh, Pallavi; Grover, Kashish (International Journal Of Community Medicine And Public Health, 2026)
The modified Kuppuswamy scale is an extensively utilized tool for assessment of socioeconomic status (SES) in urban India. The scale requires updates periodically due to inflation. This article revises the income component of this scale for the year 2026 using the most recent CPI-IW value (148.6). Application of three methods of revisions have been depicted: direct CPI conversion method, multiplication factor method, and proportional scaling method. All these methods established an upward shift in the income thresholds in all socioeconomic classes. Among the three, direct CPI conversion method provided the highest estimates, while the proportional scaling method overstated values. The multiplication factor method provided practical, well- balanced and at the same time, reproducible results, making it most feasible and apt for regular updates. This review sustains the original scale structure and also ensures relevance that is contemporary for both qualitative and quantitative public health research.